Multi-proxy evidence for human-induced deforestation and cultivation from a late Holocene stalagmite from middle Java, Indonesia - Nothstein, Arno; Fohlmeister, Jens; Mangini, Augusto; Schröder-Ritzrau, Andrea (Chemical geology, 2013)
Speleothem multi-proxy records have proved highly useful in reconstructing past changes in climatic and environmental conditions as well as karst processes, and in distinguishing between the numerous potential driving forces that influence these proxies. There is lack of such terrestrial proxies from the tropical Indo-Pacific. For the first time, we present an annual- to decadal-scale multi-proxy record of 377 samples including stable isotopes (δ18O, δ13C) and trace elements (Mg/Ca, Sr/Ca) from a Holocene calcite stalagmite from Bribin Cave, Gunung Kidul regency, middle Java, Indonesia that has grown over the last 4000years (11 230Th dates). δ18O values average −7‰ with high-frequency variability of up to 1‰, and hint at relatively stable overall climatic conditions in the tropical Indo-Pacific region during the late Holocene. The δ13C values of stalagmite JB2 are low (~−13‰) at the beginning of the record suggesting a C3-dominated rainforest cover. Strong positive covariation with Mg/Ca and Sr/Ca ratios is a stringent indication of a dominant natural control by prior calcite precipitation and water-rock interaction. However, δ13C values increase dramatically by ~4‰ from ~1.1ka to ~0.5ka, clear evidence of an anthropogenic influence through deforestation and cultivation.
Gesehen am 08.10.2021